Dealing with Feeling: Emotion, Affect, and the Qualitative Research Encounter - Rau, Asta (Qualitative Sociology Review, 2020)
Emotion and affect are different, yet intricately interwoven. Emotions such as fear, joy, or sadness are biological in as far as they are physically felt, but they are relational in as far as they are more fully experienced. Affect arises out of the relational quality of emotion—it consists of the myriad ways in which emotions are embodied, expressed, and enacted.Emotion and affect are influenced by their physical and symbolic contexts. In terms of physical context, data for this article were collected from two different research studies and several sites in the Free State Province of South Africa. Two forms of data were collected: verbal data and images/artworks. In terms of symbolic context, these verbal and visual forms of language and their functioning were explored to generate insights on the social construction of emotion and affect.Margaret Wetherell’s work provides a theoretical basis for analyzing emotion and affect. Rather than conceptualizing emotion in terms of obscure or esoteric formulations, her “practice-based” approach grounds the study of emotion by examining its manifestation in actions. When taken together, action and practice imply pattern and order, form and function, process and consequence.Both projects featured in this paper are sensitive studies that stir emotion. This is fertile ground for exploring emotion and affect in participants’ narratives. It is also fertile ground for exploring how emotion and affect may influence the qualitative researcher and the research process itself. Accordingly, this paper offers an additional layer of analysis on the functioning of intersubjectivity, power, emotion, and affect in the research encounter. Concluding insights endorse the practice of mindfulness as a fruitful approach to manage researcher subjectivity in the qualitative research encounter.